ANALISIS KENDALA PROSES PEMBELAJARAN DARING DI KELAS 2B SDN PENGADEGAN 07 JAKARTA TAHUN AJARAN 2021/2022 PADA TEMA TUGASKU SEHARI-HARI - Siti Syarah; Febrianti Yuli Satriyani (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
This background is researcher who wants to know and further describe the obstacle of online learning process in class 2B SDN Pengadegan 07 Jakarta Year 2020/2021 with a type of Descriptive Qualitative research. This research aims to explain the implementation of experienced by teachers and student, and efforts teachers take in overcoming obstacles in the online learning process in the class of 2B SDN Pengadegan 07 Jakarta Year 2020/2021. Result of research suggest that the process online learning uses only whatsapp group withput zoom, classroom and other support applications. In the learning process, surely there are obstacles faced by both teachers and students, such as mobile phone constraints, quota, learning materials, parents who cannot accompany the learning due to work, late task collection, students who lack understanding of the material. However, teachers have an effort in overcoming the obstacle, such as teachers fo not give the task collection deadline, always working with parents on the online learning, giving students a spirit in video and image.